'Ask what you can do to the Army': A textual analysis of the underground GI press during the Vietnam War. (September 2019) - Painter, Chad; Ferrucci, Patrick
This study examined the normative roles of alternative media, focusing on how the underground GI press did or did not serve these roles during the Vietnam War. The researchers conducted a textual analysis of 22 underground GI newspapers published between 1967 and 1973. Four main themes emerged from the analysis: underground GI press writers were decidedly antiwar in the stories they covered and how they wrote about them; GI writers attempted to differentiate grunts from military and civilian leaders; GI writers attempted to build communities with other military personnel as well as civilians; and instances of censorship and persecution were widely reported. The results were then analyzed through the theoretical lens of the monitorial–disseminator, facilitative–mobilizer, radical–adversarial, and collaborative–interpretive roles of media.